2013
DOI: 10.1111/cei.12072
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune function monitoring after allogeneic haematopoietic cell transplantation: evaluation of a new assay

Abstract: SummaryManaging the patient's immune system after haematopoietic cell transplantation (HCT) is a challenge, mainly in the unstable period immediately after the transplant. Currently there is no standardized non-invasive diagnostic tool for the evaluation of immunological complications such as graft-versushost disease (GVHD) and for managing the cellular immune function of the transplant recipient. The ImmuKnow assay for cellular immune function monitoring has been incorporated successfully into the clinical fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The Cylex ImmuKnow ® is another immune monitoring assay, which after stimulation with PHA measures intracellular adenosine triphosphate levels in CD4+ T-cells ( 24 ). Several studies in the HSCT population did not demonstrate any additional clinical value of the ImmunKnow assay ( 11 , 25 , 26 ). More complex biomarkers such as T-cell immunoglobulin and mucin-domain containing 3 (TIM3), interleukin-6, soluble tumor necrosis factor receptor 1, and plasma suppression of tumorigenicity 2 have shown some promise in predicting AGVHD and NRM ( 3 , 5 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The Cylex ImmuKnow ® is another immune monitoring assay, which after stimulation with PHA measures intracellular adenosine triphosphate levels in CD4+ T-cells ( 24 ). Several studies in the HSCT population did not demonstrate any additional clinical value of the ImmunKnow assay ( 11 , 25 , 26 ). More complex biomarkers such as T-cell immunoglobulin and mucin-domain containing 3 (TIM3), interleukin-6, soluble tumor necrosis factor receptor 1, and plasma suppression of tumorigenicity 2 have shown some promise in predicting AGVHD and NRM ( 3 , 5 ).…”
Section: Discussionmentioning
confidence: 96%
“…Potential biomarkers should ideally be easy to perform, be reproducible, and accurately predict outcomes such as AGVHD ( 3 , 5 ), infection ( 9 , 22 ), and survival ( 3 , 9 ). Candidate biomarker targets have included T-cell subsets ( 7 , 23 ), functional immune assays ( 11 , 23 ), inflammatory cytokines ( 22 ), and interleukin receptors ( 5 ). T-cell subset numbers, particularly higher CD8+ T-cells but not CD4+ T-cells, at day 90 were recently observed to predict enhanced survival in a cohort of HSCT recipients but immune function was not assessed ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides infections, another detrimental complication to HCT is acute GvHD, where alloreactive donor‐derived T cells recognize recipient cells as foreign and initiates a cytotoxic and inflammatory response resulting in organ damage, typically in the skin, gut and/or liver 44 . A previous study of CD4+ T cell reactivity found that patients with acute GvHD had a markedly increased immune response to phytohemagglutinin stimulation 24 . In our study, a single patient had acute GvHD at the time of whole blood sampling, and while this patient had higher‐than‐average signatures of cytokine responses to R848 and HKCA stimuli, other GvHD‐free patients exhibited similar patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies of the functional immune reconstitution at different timepoints after HCT have investigated (a) the reactivity of CD4+ T cells based on the amount of adenosine phosphate secreted upon phytohemagglutinin stimulation [21][22][23][24] ; (b) the virus-specific reactivity of CD8+ T cells based on the release of interferon-γ upon stimulation with viral antigens [25][26][27][28][29][30] ; (c) the pathogen-specific proliferative and cytokine responses of peripheral blood mononuclear cells after culturing 31 ; or (d) the phagocytic, migratory and stimulusspecific oxidative capacity of neutrophils and monocytes 32,33 ; among other approaches. While these approaches-to evaluate the post-HCT functional immune reconstitution-are valuable when investigating pathogen-or immune cell-specific responses, our study demonstrates the feasibility of obtaining a more global screening of the circulating immune cells post-HCT, revealing a broad array of cytokine responses elicited through multiple immunologic signalling pathways.…”
Section: Discussionmentioning
confidence: 99%